Evaluation of the Resilient Modulus of Hot-Mix Asphalt Made with Recycled Concrete Aggregates from Construction and Demolition Waste - Galan, Juan J. (2021)
This paper reports the inﬂuence of the percentage of recycled aggregate (RCA) fromconstruction and demolition waste (C&DW) together with the percentage of binder (L), curing time(t) and temperature (T) of the samples on the stiﬀness of a hot asphalt mixture. The study was carriedout using the response surface methodology (RSM). The resilient modulus was chosen to estimate thestiﬀness of the mixture. The percentages of RCA studied were 0% (control), 5%, 10%, 20% and 30%,whilst 3.5%, 4% and 4.5% were those chosen for the binder content. Before compacting the samples,they were left into the oven to cure. Curing time, or pretreatment time, were set at 0 (control), 2 and4 h. The samples were subjected to temperatures of 0, 10 and 20◦C. The natural aggregate is of thehornfels type. All the specimens studied showed high stiﬀness at low temperatures. According tothis research, temperature proved to be the most inﬂuential factor on the decrease in the resilientmodulus and, conversely, the percentage of recycled aggregate is not a signiﬁcant factor in the rangeof values studied.